2016
DOI: 10.1007/s00404-016-4102-1
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of intraperitoneal cytology during laparoscopic surgery of uterine cancer

Abstract: During laparoscopic surgery of early stage endometrial and cervical cancer, only one conversion of cytology was detected, which proves that laparoscopy does not appear to increase the intraoperative tumor cell dissemination or rate of positive cytological results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…They concluded that laparoscopy does not appear to increase the rate of intraoperative tumor cell dissemination. [31] In our study, among the 15 patients who had positive intraperitoneal cytology on entering the peritoneal cavity, 10 converted to negative intraperitoneal cytology after hysterectomy. Surgery procedures, including washing and suction for keep the field clean, may reduce the number of cancer cells in the peritoneal cavity.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…They concluded that laparoscopy does not appear to increase the rate of intraoperative tumor cell dissemination. [31] In our study, among the 15 patients who had positive intraperitoneal cytology on entering the peritoneal cavity, 10 converted to negative intraperitoneal cytology after hysterectomy. Surgery procedures, including washing and suction for keep the field clean, may reduce the number of cancer cells in the peritoneal cavity.…”
Section: Discussionmentioning
confidence: 75%
“…von Heesen et al [31] reported on the conversion of pelvic cytology during laparoscopic surgery in endometrial cancer patients. In this study, intraperitoneal cytology at the beginning and end of surgery was assessed.…”
Section: Discussionmentioning
confidence: 99%